SPEAKING LEARNING ACTIVITIES YANG DIGUNAKAN DALAM BELAJAR SPEAKING 1 MAHASISWA TBI STAIN PAMEKASAN - Hasan Basri (IAIN MADURA, 2015)
Speaking is important language skill in language learning process. The success of study English reflects to a mastery of speaking skill. In order to, to choose appropriate learning activities will help the students comprehend the speaking skill well. There are effective steps of learning activity to facilitate the students to study speaking; memory, cognitive, and compensation learning activities. The combination of learning activity can facilitate the speaking learning process that is not only finding the meaning, but also comprehend the purpose and the use, and can be used in daily communication.